Evaluation of Iron Deficiency Anemia in Pregnancy: Iron Deficiency Anemia in Pregnancy - Asghar, Sadia; Azmat, Saddiqa; Rasheed, Saima; Javaid, Muhammad Faisal; Maqbool, Rimsha; Anwar, Maria (Pakistan Journal of Health Sciences, 2024)
Anemia in pregnancy was the common nutritional deficiency and a frequent medical concern that leads to numerous known complications, impacting both maternal and fetal health. Objective: To evaluate the biochemical parameters such as serum Iron, Ferritin TIBS and TfS in anemic and non-anemic pregnant women. Methods: In this cross-sectional study, pregnant women age 18-45 years attending the gynecological department of Niazi welfare foundation teaching hospital, Sargodha from April 2023 to January 2024 were included. Serum iron, ferritin, total iron-binding capacity, and transferrin saturation were assessed from blood samples. Independent sample t-test in SPSS version 26.0 was applied to see significant difference in biochemical parameters at value of <0.05. Results: Findings revealed mean hemoglobin level of 10.26 ± 1.52 g/dl in all participants. Anemic results were found in majority, accounting for 268 (70.9%) cases. Among these anemic patients, 149 (55.5%) had mild anemia, 107 (40%) had moderate anemia, and 12 (4.5%) had severe anemia. Anemic patients had significantly lower serum ferritin level (p = 0.02), serum iron (p < 0.001), and transferrin saturation (p < 0.002) than non-anemic patients. Additionally, total iron-binding capacity, (p < 0.001) indicated the anemic status of the pregnant women. Conclusions: Biochemical parameters of pregnant women with anemia were reduced compared to those without anemia. Healthcare providers should closely monitor pregnant women with reduced biochemical levels to prevent complications for both the mother and the fetus.